High Fibrinogen to Albumin Ratio: A Novel Marker for Risk of Stroke-Associated Pneumonia? - Lin, Gangqiang; Hu, Minlei; Song, Jiaying; Xu, Xueqian; Liu, Haiwei; Qiu, Linan; Zhu, Hanyu; Xu, Minjie; Geng, Dandan; Yang, Lexuan; Huang, Guiqian; He, Jincai; et al. (Frontiers in Neurology, 2022)
Background: Stroke-associated pneumonia (SAP) is associated with poor prognosis after acute ischemic stroke (AIS). Purpose: This study aimed to describe the parameters of coagulation function and evaluate the association between the fibrinogen-to-albumin ratio (FAR) and SAP in AIS patients. Patients and methods: A total of 932 consecutive AIS patients were included. Coagulation parameters were measured at admission. All patients were classified into two groups according to the optimal cutoff FAR point at which the sum of the specificity and sensitivity was highest. Propensity score matching (PSM) was performed to balance potential confounding factors. Univariate and multivariate logistic regression analyses were applied to identify predictors of SAP. Results: 100 (10.7%) patients were diagnosed with SAP. The data showed that fibrinogen, FAR, and D-dimer, PT, aPTT were higher in SAP patients, while albumin was much lower. SAP patients showed a significant increased FAR when compared with non-SAP (P < 0.001). Patients were assigned to groups of high FAR (≥0.0977) and low FAR (<0.0977) based on the optimal cut-off value. PSM analysis further confirmed the association between FAR and SAP. After adjusting for confounding and risk factors, multivariate regression analysis showed that the high FAR (≥0.0977) was an independent variable predicting the occurrence of SAP (odds ratio =2.830, 95%CI = 1.654-4.840, P <0.001). In addition, the FAR was higher in the severe pneumonia group when it was assessed by Pneumonia Severity Index (P=0.008). Conclusions: High FAR is an independent potential risk factor of SAP, which can help clinicians identify high-risk SAP patients after acute ischemic stroke. Keywords: acute ischemic stroke, stroke-associated pneumonia, coagulation, inflammation, fibrinogen, albumin